Aggressive diuretic therapy for a large solitary lung lesion - Mohd Firdaus, Mohd Al-Baqlish; Zulkafl, Hazira; Said, Mohd Ridzuan; Hadi, Mohd Firdaus; Sukhari, Samshol; Arjan Singh, Ramesh Singh (Malaysian Medical Association, 2020)
SUMMARY Pseudotumour of the lung is a rare chest x-ray finding among patients who present with fluid overload. It is caused by loculated pleural effusion in the lung fissures. Unfortunately, the occurrence of pseudotumour can be misleading and sometimes can lead to unnecessary investigation and emotional stress to the patient. We present here a case of a 61-year-old gentleman with a known history of hypertension, diabetes mellitus and dyslipidemia who presented at University Malaya Medical Centre with symptoms of fluid overload and a right middle lobe mass on chest x-ray. The right middle lobe mass disappeared entirely after being treated with aggressive diuretic therapy. A diagnosis of pseudotumour was made and described in this case report